Peculiarities of leukocyte apoptosis modulation in children with pyelonephritis - I. А. Marchenko; L. O. Babiichuk; M. M. Mishyna; N. I. Makieieva; P. M. Zubov (Regulatory Mechanisms in Biosystems, 2020)
One of the leading places among inflammatory diseases of the urinary tract of children belongs to pyelonephritis, the course of which presents in most cases as a severe infectious disease threatening the patient’s life, which is the main reason for development of chronic kidney failure. This study was conducted to compare apoptosis stages in peripheral blood of children of different age categories with pyelonephritis depending on etiological factor and complications. The problem of mechanisms underlying immune system misregulation, especially functional activity of leukocytes in children with pyelonephritis, have not been explored in recent years. Assessment of leukocytes (neutrophils) apoptosis stages in peripheral blood of children of different age categories with pyelonephritis depending on complications and etiological factor was the aim of present study. The children's peripheral blood samples were analysed and assessed using a flow cytofluorimeter. The present study demonstrates an increase of the level of apoptotic cells at an early stage of apoptosis in children of all age categories with chronic pyelonephritis, which can be explained by associations of a wide range of pathogens and the presence of sequelae. An increase in the number of apoptotic cells in the late stage of apoptosis is observed in children aged 1 month – 8 years, in children 8–18 years, the amount of apoptotic cells is reduced by 1.5 times. The study of apoptosis stages allows complete characterization of the dynamics of the apoptotic process and supplementation of the pathogenesis of pyelonephritis in children. Such studies will make it possible to affect apoptosis modulation to regulate or correct it and encourage the finding of innovative solutions in the treatment related to influence on the immune response. We conclude that enhancement of peripheral blood leukocyte apoptosis in chronic form of pyelonephritis especially in young children is due to the polyetiology of this form of pyelonephritis and the development of complications.